Origin of invasive Florida frogs traced to Cuba - Heinicke, Matthew P. (The Royal Society, 2011)
Two of the earliest examples of successful invasive amphibians are the greenhouse frog (Eleutherodactylus planirostris) and the Cuban treefrog (Osteopilus septentrionalis) in Florida. Although both are generally assumed to be recent introductions, they are widespread on Caribbean islands and also have been proposed as natural colonizers. We obtained nucleotide sequence data for both species and their closest relatives in their native and introduced ranges. Phylogenetic analyses trace the origin of E. planirostris to a small area in western Cuba, while O. septentrionalis is derived from at least two Cuban sources, one probably a remote peninsula in western Cuba. The tropical-to-temperate invasion began with colonization of the Florida Keys followed by human-mediated dispersal within peninsular Florida. The subtropical Keys may have served as an adaptive stepping stone for the successful invasion of the North American continent.